Where are They Going: Emerging Mobility Patterns of Generation Y in Canada - Agarwal, Ajay; Rasheed, Fathimah Tayyiba (Canadian Planning and Policy / Aménagement et politique au Canada, 2025)
Using 2006 and 2016 household travel survey data from the Greater Toronto Area, this paper examines emerging mobility patterns of Generation Y – those born between 1980 and 2000 – also called the millennials. The paper finds that lower reliance on personal automobile, greater use of public transit and active transport modes as compared to preceding generation reported in earlier research persists. While use of automobile does increase with age in Generation Y, it is still lower than that of the preceding generation. The findings give hope for further reduction in personal automobile use, and greater use of sustainable transport modes including walking, bicycling, and public transit in the future. It is an opportune time for transportation policy planners to support use of sustainable transport modes with appropriate policy interventions.